Effect of Regenerative Organic Rankine Cycle (RORC) on the Performance of Solar Thermal Power in Yogyakarta, Indonesia - Ghalya Pikra; Andri Joko Purwanto; Adi Santoso (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2013)
This paper presents effect of Regenerative Organic Rankine Cycle (RORC) on the performance of solar thermal power in Yogyakarta, Indonesia. Solar thermal power is a plant that uses solar energy as heat source. Indonesia has high humidity level, so that parabolic trough is the most suitable type of solar thermal power technology to be developed, where the design is made with small focal distance. Organic Rankine Cycle (ORC) is a Rankine cycle that use organic fluid as working fluid to utilize low temperature heat sources. RORC is used to increase ORC performance. The analysis was done by comparing ORC system with and without regenerator addition. Refrigerant that be used in the analysis is R123. Preliminary data was taken from the solar collector system that has been installed in Yogyakarta. The analysis shows that with 36 m total parabolic length, the resulting solar collector capacity is 63 kW, heat input/evaporator capacity is determined 26.78 kW and turbine power is 3.11 kW for ORC, and 3.38 kW for RORC. ORC thermal efficiency is 11.28% and RORC is 12.26%. Overall electricity efficiency is 4.93% for ORC, and 5.36% for RORC. With 40°C condensing temperature and evaporation at 10 bar saturated condition, efficiency of RORC is higher than ORC. Greater evaporation temperature at the same pressure (10 bar) provide greater turbine power and efficiency.